MAPPING THE VARIOUS FORMS OF VIOLENCE AGAINST VULNERABLE GROUPS IN THE CONTEXT OF SEXISM - Nizmi, Yusnarida Eka; Wahyudi, Herry; Hasibuan, Ahmad Ibrahim Roni Surya; Yulia, Rahmi; Takwa, Tuah Kalti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This paper will analyze how sexism is closely correlated with violence that can endanger vulnerable groups, both men and women. The violence referred to here is psychological violence. People tend to more easily recognize physical violence compared to psychological violence, which ranks first in destroying someone's mental health. This paper will also elaborate on how the influence of gender discrimination determines the presence or absence of violence in the scope of sexist behavior toward the lives of vulnerable groups. Sexism and gender stereotypes serve as the primary references in classifying what behaviors are acceptable and what are not, what should be done, and what should be abandoned by both men and women. These gender stereotypes bring consequences for anyone who is not consistent with the existing and socially accepted patterns. This paper selects the elaboration of the concept of sexism as the primary analytical tool using a qualitative method. Data is collected by conducting in-depth interviews with 86 selected informants and analyzing references and written documents related to sexism and violence. This paper demonstrates that violence in the context of sexism will continue to claim victims from vulnerable groups if the values of violence within sexism are not stopped.